The Oxford handbook of the corporation - Clarke, Thomas, 1950-; O'Brien, Justin; O'Kelley, Charles R. 1946- (Oxford handbooks online., 2019)
This handbook assesses the contemporary relevance, purpose, and performance of the corporation. The corporation is one of the most significant, if contested, innovations in human history, and the direction and effectiveness of corporate law, corporate governance, and corporate performance are being challenged as never before. Continuously evolving, the corporation as the primary instrument for wealth generation in contemporary economies demands frequent assessment and reinterpretation. The focus of this work is the transformative impact of innovation and change upon corporate structure, purpose, and operation.